Inheritance of Blast Resistance (Pyricularia grisea Sacc.) on Interspecific Crossing between IR64 and Oryza rufipogon Griff - DWINITA WIKAN UTAMI; HAJRIAL ASWIDINNOOR; SUGIONO MOELJOPAWIRO; IDA HANARIDA; REFLINUR REFLINUR (HAYATI Journal of Biosciences, 2006)
Blast disease affected by Pyricularia grisea causes high percentage of yield losses in rice production. The improvement of durable Blast resistance is difficult due to the complexity of the inheritance of this trait. This study was conducted to evaluate the genetic control and inheritance of Blast resistance trait in interspesific population between IR 64 (accepted Indonesian rice type, medium resistant to Indonesian Blast pathogen) and Oryza rufipogon (AA genome; acc. No.IRGC#105491; donor for Blast resistance). Six populations, i.e. P1, P2, F1, F2, BCP1, and BCP2, were inoculated with three Indonesian races of Blast pathogen. The disease intensity was determined on the basis of disease leaf area (DLA). The three types of gene interactions (additive, dominance, and epistatis) were significantly involved in this trait. Among the digenic epistasis interactions, all of the additive x additive [i], additive x dominance (j) and dominance x dominance (l) contributed to the trait. Broad-sense heritability ranged from 50.30 up to 91.20%, while the narrow heritability ranged from 16.98 up to 73.20%. The presence of additive gene effect indicated that selection of this trait is promising. Key words: inheritance, Blast resistance, wild rice, Oryza rufipogon